The Relationship of Physical Activity to HDL Levels and Dietary Patterns to Uric Acid Levels among Hypertensive PROLANIS Patients - Dewi Nurjanah Jaya Saputri; Lutfi Kurniawati; Tasrif Ahmad (Jurnal Biologi Tropis, 2026)
Hypertension is a chronic condition associated with metabolic disorders, including decreased High-Density Lipoprotein (HDL) levels and elevated uric acid levels, which may increase cardiovascular risk. Physical activity and dietary patterns are lifestyle factors believed to influence these metabolic parameters, although previous findings remain inconsistent. This study aimed to examine the relationship between physical activity and HDL levels, as well as dietary patterns and uric acid levels, among hypertensive patients participating in the Chronic Disease Management Program (PROLANIS) at Klinik Griya Sehat Colomadu. An observational study with analytic elements utilizing both cohort and cross-sectional methods was carried out with 30 participants chosen through purposive sampling. The level of physical activity was evaluated using the International Physical Activity Questionnaire (IPAQ), while eating habits were analyzed through a Food Frequency Questionnaire (FFQ) that was substantiated by a 24-hour food recall. HDL and uric acid concentrations were determined using enzymatic methods in a laboratory. The data was examined employing the Spearman correlation test and Fisher’s Exact Test at a significance threshold of 0.05. Findings indicated that the average HDL level was greater in the group engaging in moderate physical activity compared to the one with low physical activity; nevertheless, no significant relationship was observed (p = 0.091). Dietary patterns were also not significantly associated with uric acid levels (p = 0.155). In conclusion, physical activity was not significantly related to HDL levels, and dietary patterns were not significantly related to uric acid levels among hypertensive PROLANIS patients.